SELF-CONFIDENCE DAN SELF-DISCLOSURE PADA MURID BARU DI MASA PANDEMI COVID-19 - Walda Isna Nisa; Nurul Lail Rosyidatul M (Program Studi S1 Psikologi, 2022)
Abstract Most individuals build peer relationships where there is someone who is fun to be with and can make individuals comfortable being themselves. In line with the development of individual relationships tend to require acceptance from the environment. This study aims to determine whether there is a relationship between self-confidence and self-disclosure in new students at SMK X Malang Regency. This study uses a quantitative approach with the population in this study is the new students of SMK X in 2020/2021 as many as 114 people. The data collection technique uses a Likert scale instrument consisting of a self-confidence scale consisting of 30 items and a self-disclosure scale consisting of 30 items that have been tested for reliability and validity. The data analysis technique used the Pearson product moment correlation technique with SPSS version 22 for windows. The results showed that there was a relationship between self-confidence and self-disclosure. The higher the self-confidence, the higher the self-disclosure and vice versa. Individuals can develop their social skills during online schooling to establish relationships or interactions through self-disclosure by increasing their self-confidence.